Manual of Operations for the Schools-on-the-Air on Smart Rice Agriculture in the Philippines - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The Department of Agriculture recognized the manual of operations as the official guide of the national SOA program under the Rice Competitiveness Enhancement Fund (RCEF). The SOA-SRA, under the RCEF extension service component, aims to provide a learning program in rice producing provinces, targeting 300,000 rice farmer-enrollees within two years.